UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL SCIENTIFIC PADA MATA PELAJARAN IPA KELAS IV SD NEGERI 047166 SUKADAME TAHUN PEMBELAJARAN 2018/2019 - GINTING, ICHA TERESIA (Jurnal Ilmiah Aquinas, 2019)
This study aims to improve student learning outcomes in science subjects in grade IV SD Negeri 047166 Sukadame by using a Scientific model. Subjects in this study were fourth grade students totaling 28 students and the object of this study was to improve student learning outcomes by using a Scientific model. This type of research is Classroom Action Research (CAR) which is divided into 3 stages, namely general ideas, exploration, and action plans. Data collection techniques used are tests and observations, tests are given as many as 10 questions in multiple choice form. The questions given were pretest, post cycle I and post cycle II. While observation includes observing teacher activities and observing student activities in the learning process.The results of the study indicate an increase in student learning outcomes. In the pretest, it was found that the average value of 50 and the level of completeness in classical was 17.9%. In cycle I experienced an increase after using a Scientific model with an average value of 72.14, with a classical completeness level of 39.3%. And after the action taken and given post cycle II, it was obtained as many as 25 students who completed their learning outcomes and 5 students who did not complete their learning outcomes with the average posttest value of cycle II increased to 84.2% and the classical completeness level reached 82.1% . From the results obtained it can be concluded that the Scientific model can improve student learning outcomes in class IV SD Negeri 047166 Sukadame Learning Year 2018/2019. Based on the results of the study, the teacher is advised to use a Scientific model because it is proven to improve student learning outcomes.